Optimal Outcomes Reporting (OOR): A New Value–Based Metric for Outcome Reporting Following Cleft Palate Repair. (January 2021) - Meara, John G.; Hughes, Christopher D.; Sanchez, Karl; Catallozzi, Liza; Clark, Roseanne; Kummer, Ann W.
Objective: Palatoplasty outcome measurements vary widely among institutions. A standardized outcome metric would help provide quality benchmarks. Design: Retrospective review of primary palatoplasty patients from 2007 to 2013. Setting: Tertiary care children's hospital. Main Outcome Measures: We created a novel conceptual quality metric called "OOR" (Optimal Outcome Reporting). Optimal Outcome Reporting is designed to reflect the percentage of patients with cleft palate who experience the best outcomes: one operation, velar competence by age 5 years, and no unintended palatal fistula. Results: Optimal Outcome Reporting was 72.3% (68/94). Eight patients had "suboptimal" outcomes for having undergone more than one operation. Eighteen patients failed for velar incompetence. No additional patients fell out of the algorithm for fistula. A significantly higher proportion of nonsyndromic patients demonstrated an "optimal" result compared to syndromic patients (61/80, 76.3% vs 7/14, 50.0%; P = .04). Patients who required more than one procedure had significantly more clinic visits (32.6 vs 14.9; P < .01) and accrued higher costs compared to "optimal" patients (US34 019.88 vs US15 357.25; P < .01). Conclusions: Optimal Outcome Reporting represents a novel quality metric that can provide meaningful information for patients with cleft palate. Optimal Outcome Reporting utilization can help cleft centers adopt changes that matter to patients and their families. By allowing for cross-institutional comparisons in a clear and objective manner, OOR can promote competition, innovation, and value in cleft palate care.